The Impact of Credit Risk Management on the Financial Performance of the Banks Listed on the Dhaka Stock Exchange: A Two-Step System Generalized Method of Moments Panel Data Analysis - Hossain, Mohammad Kamal; Golder, Uttam (The Economics and Finance Letters, 2022)
Prior Bangladeshi studies on the relationship between credit risk management and the financial performance of listed banks suffered from a dynamic endogeneity bias, which led to misleading conclusions. As a result, this study examines the impact of credit risk management on the financial performance of banks listed on the Dhaka Stock Exchange for the period from 2011 to 2018. The equity multiplier ratio (EMR), capital adequacy ratio (CAR), non-performing loan (NPL) ratio, interest coverage ratio (ICR), and provision for credit losses to total credit (PCLTC) are proxies for credit risk management. The study characterizes banks’ financial performance from three perspectives: bank management, as indicated by return on equity (ROE); the market, as indicated by Tobin’s Q (TQ); and shareholder value, as indicated by economic value added (EVA-ln). The study sample comprises 29 of the 30 listed banks, and the two-step system generalized method of moments (GMM) model is used to test the hypotheses. This study finds mixed results, i.e., none of the credit risk variables used in this study, with the exception of ICR, affect the sampled banks’ performance equally from each of the three perspectives. Particularly, the results show that ICR has a significant positive impact on all measures of banks’ financial performance, whereas PCLTC has no impact on any measure of financial performance. The EMR has a significant positive impact on ROE but does not affect TQ and EVA-ln. CAR has been shown to improve ROE and TQ while having an insignificant effect on EVA-ln. The NPL ratio has a negative effect on ROE but does not affect TQ and EVA-ln.